Assessment of wound healing of tagged gray (Eschrichtius robustus) and blue (Balaenoptera musculus) whales in the eastern North Pacific using long‐term series of photographs. Issue 1 (3rd September 2017) - Norman, Stephanie A.; Flynn, Kiirsten R.; Zerbini, Alexandre N.; Gulland, Frances M. D.; Moore, Michael J.; Raverty, Stephen; Rotstein, David S.; Mate, Bruce R.; Hayslip, Craig; Gendron, Diane; Sears, Richard; Douglas, Annie B.; et al.
Abstract: Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.